Risk of Nitrate Residues in Food Products and Drinking Water - Yousefi, Hossein; Karimi Douna, Bahareh (Asian Pacific Journal of Environment and Cancer, 2023)
Although nitrate is the essential nutrient of our body, the excess amount of it as residues strongly causes disease. Nitrate comes from plant and animal foods that are vital to our metabolism. The nitrate is absorbed through the soil by plants and becomes an herbal protein that is placed in the food chain. If the nitrate is absorbed more than the plant requirement, it will be accumulated into the plant’s organs. Since nitrogen fertilizers increase the weight and yield of the plants, farmers consume large amounts of which. Hence, we investigate the consumption of nitrogen fertilizers in the world and the standard allowable residual nitrate in food and water considering the accumulation of nitrate in water and food. Excess amount of nitrate in the soil enters the drinking water after leaching or directly transported from groundwater to surface water and drinking water. The entry of the excess amount of nitrate from food products and drinking water into our bodies causes dangerous diseases such as different types of cancers, methemoglobinemia, osteoporosis, kidney stones, and some other diseases. The present article, besides indicating the benefits of nitrate for Treatment purposes and demonstrating the state of nitrate accumulation in food and water as well as its standards, deals with diseases caused by it and presents some remedies to reduce the risks.